Value of the individual components subject training gymnasts according to the survey of coaches with different skills - Andreeva, N. O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: assess the significance of the individual components subject training gymnasts according to the survey of coaches with different skills.